Asuhan Keperawatan Keluarga Tahap Lanjut Usia Dengan Intervensi Air Perasan Herbal Jahe Untuk Mengurangi Nyeri Gastritis Pada Ny R - Ely Nurjanah; Alfika Safitri; Rina Puspita Sari; Muhammad Hasan Basr (STIKes Ibnu Sina Ajibarang, 2023)
The last stage of family development begins when one partner retires, then one partner dies. Gastritis cases in the world are 1.8-2.1 million per year, according to Health et al., (2021), in Indonesia alone gastritis sufferers are estimated to be 40.8 reaching a prevalence of 274,396 among 238,452,952 residents in several regions of Indonesia. Ginger Plant Ginger (Zingiber officinale), is a rhizome plant which is very popular as a spice and medicinal ingredient. The rhizome is in the form of a bulging finger in the middle sections. The dominant spicy taste is caused by a ketone compound called zingeron. The aim is to carry out Nursing Care for Patients with Gastritis with Chronic Pain in Kp Bayur Ds Periuk Jaya Rt 01 RW 04 periuk jaya tangerang. The method used in this study is data collection through interviews, observation, physical examination and documentation while the analysis used is data, data reduction, data study. The results obtained from this study are nursing problems that arise in Mrs. R, namely chronic pain, ineffective health management. The highest scoring based on priority diagnoses is Chronic Pain. On the third day based on priority diagnosis of Chronic Pain, and Ineffective Health Management. The evaluation found that the nursing problem of Chronic Pain was resolved marked by the family being able to make herbal medicine from ginger concoction. Ginger herbal therapy techniques have an influence on reducing pain in gastritis patients